Intelligent Risk-Aware SAP Cloud Framework Leveraging Ethical AI and Automated Machine Learning for Secure Enterprise Transformation (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The integration of Artificial Intelligence (AI) and Automated Machine Learning (AutoML) into SAP cloud ecosystems has revolutionized enterprise operations, enabling intelligent automation, real-time analytics, and predictive governance. However, these advancements also introduce ethical, operational, and compliance-related challenges that necessitate a holistic and risk-aware framework. This paper proposes an Intelligent Risk-Aware SAP Cloud Framework that leverages ethical AI and AutoML to achieve secure, transparent, and adaptive enterprise transformation. The framework combines predictive intelligence with governance mechanisms to identify, assess, and mitigate operational and compliance risks dynamically within SAP Cloud environments. The proposed architecture is structured into four layers: (1) Cloud Infrastructure and Integration Layer, supporting modular, multi-cloud SAP deployments; (2) AutoML Layer, automating model training, validation, and optimization for continuous risk detection; (3) Ethical AI Governance Layer, embedding transparency, fairness, and explainability into automated decision systems; and (4) Risk Intelligence and Compliance Layer, ensuring ongoing monitoring of data access, segregation of duties (SoD), and compliance alignment with ISO and GDPR standards. A prototype implementation on the SAP Business Technology Platform (BTP) demonstrates improvements in predictive accuracy, compliance adherence, and decision explainability. The results show that ethical AI combined with automated learning processes can effectively balance innovation and governance, reducing enterprise risks while maintaining performance and transparency. This study contributes a structured approach to developing risk-aware, ethically guided SAP automation systems that align technology adoption with corporate governance, security, and accountability principles.
Keywords: SAP Cloud; AutoML; ethical AI; enterprise transformation; predictive analytics; governance; risk management; explainability; compliance; secure automation